Features of the course and treatment of JIA-associated uveitis - M.V. Panchenko; N.S. Shevchenko; M.V. Demianenko; Honchar O.M; L.G. Avilova (Ukrainian Society of Ophthalmologists, 2019)
Purpose: To investigate the features of the clinical course of and the state of eye care for patients with juvenile idiopathic arthritis (JIA)-associated uveitis (JIA-U). Materials and Methods: We analyzed the results of monitoring 121 patients aged 7 to 18 years with JIA. Twenty one (17.35%) of these had uveitis. Results: In 17 (80.95%) of the examined JIA-U patients, JIA onset age was younger than 6 years, and mean JIA onset age was significantly younger than in JIA patients without uveitis (2.89±0.26 years vs 6.43±0.4 years, р<0.05). Most (85.7%) JIA-U patients were asymptomatic. Chronic keratic precipitates and posterior synechiae were found in 38.09% and 42.85%, respectively, of cases. Uveal cataract was the most common complication (57.14%), followed by corneal degeneration (33.33%), macular edema (28.57%), ocular hypertension/ secondary glaucoma (19.05%), optic nerve edema (14.28%), hypotony (14.28%), vitreous fibrosis (9.52%), and retinal detachment (4.76%). The frequency of administration of biologics was 57.14%. The mean time from disease onset to administration of biologics in our JIA-U patients (2.67±0.79 years) was 2.5 times less than the value for JIA-U patients from all over Ukraine (6.9 years), indicating that biologics were timely administered. Conclusion: Patients with the condition are commonly asymptomatic and have frequent ocular complications, with uveal cataract being the most common, followed by corneal degeneration and macular edema.